Biopest Product Franchise Business Assistance in The Creative Economy of Farmer Groups, Ponggok District, Blitar Regency - Dwi Irnawati; Reza Anggapratama (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Farmer Group of Ponggok District, Blitar Regency has now used coconut shells which used to be waste around the Blitar community. And from the coconut shells produce natural pesticide products called BIOPEST products. BIOPEST products have been marketed among themselves and the environment of the city of Blitar. And the farmer group wants to further market its target market reach through a franchise business so that it is more developed and better known by the wider community and improves the economy in Blitar city, especially in Ponggok district. But the farmer group has obstacles related to branding, distribution, marketing and making booths for the BIOPEST product franchise business. Because the understanding of the business members of the farmer group is still insufficient. So that this activity provides assistance for these farmer groups to better understand and practice the BIOPEST product franchise business. The method used in this activity is to start with a survey first to identify the current business situation of the Ponggok sub-district farmer group, after that socialization is held to provide an understanding of the importance of franchise business in a business, then it will be accompanied for packaging and branding, making booths for selling and marketing through social media and distribution of franchise products to consumers. And the last is an evaluation by providing questionnaires or tests that must be filled out by all participants. This test is given at the beginning and end of mentoring to find out how much the participants' understanding of the assistance has increased. The result of the evaluation is that participants experienced an increase in understanding of about 50% from before. So that this mentoring activity is effective in providing understanding accompanied by packaging practices, branding, booth making and how to market BIOPEST products through social media.